APLIKASI MODUL SENSOR CAHAYA GY-302 BH1750 DAN SENSOR JARAK ULTRASONIK HC-SR04 PADA EKSPERIMEN FOTOMETER BERBASIS MIKROKONTROLER ARDUINO UNO - Muryani, Sri; Sumariyah, Sumariyah (BERKALA FISIKA, 2020)
This study aims to implement the GY-302 BH1750 light sensor module and the HC-SR04 ultrasonic proximity sensor to determine the illumination of the test lamp and distance in an Arduino Uno-based photometer experiment. There were aluminum rail with a total length of 100 cm and the sensor rail with length of 80 cm in the mechanical device of this photometer, while the sensor was made from acrylic. The working principle of this photometer experiment tool began with a DC motor that puts the sensor at the initial state near the limit switch 1. The sensor measured the illumination and distance to display on the LCD. The motor moved the sensor away from the lamp and the sensor stopped every 5 cm change in distance, then the sensor detected the distance and illuminates in which their values were displayed on the LCD. The motor returned to the limit switch 1 when it hits at the limit switch 2 of the limit finish. The average error value of the ultrasonic sensor calibration was 1.35% with the correlation value of 0.9997. Meanwhile the average error value of the light sensor calibration was 3.39% with the correlation value of 0.9867. The results of this photometer experiment showed that the intensity of the yellow, clear, red, and blue lights are 7.91, 6.42, 2.10, and 0.49 Cd with error values of 15.66, 11.61, 9.12, and 7.34% and the correlation values of 0.9954, 0.9983, 0.9987, 0.9981, respectively.Keywords: Photometer, light sensor, proximity sensor